PENGABDIAN UNTUK MENINGKATKAN MUTU PRODUK, PEMASARAN DAN PENDAPATAN HANDICRAFT GHANIM - Hartati, Fadjar Kurnia; Sigit, Bambang; Besari Dj, Arlin (Perkumpulan Legowo Cerdas Sejahtera, 2024)
The purpose of this service activity is to help Partners in efforts to improve quality, marketing and ultimately increase Partners' income. The implementation of community service activities is carried out by counseling, mentoring, and direct practice on how to improve marketing, prepare workshops, increase product attractiveness and obtain capital. This service activity has the main work results, namely Partners already have marketing methods for the work, have a place to carry out adequate production activities and showrooms/workshops, have more types and numbers of products and are more attractive to consumers, and have received capital assistance that will used to develop their business.